225k views
2 votes
Help me please!!!!!!!!!!!!!

Help me please!!!!!!!!!!!!!-example-1

2 Answers

3 votes

Answer:

A

Explanation:

Using the midpoint formula

[ 0.5(x₁ + x₂), 0.5(y₁ + y₂ ) ]

with (x₁, y₁ ) = (- 4, 6) and (x₂, y₂ ) = (4, - 2), then

midpoint = [ 0.5(- 4 + 4), 0.5(6 - 2) ] = [0.5(0), 0.5(4) ] = (0, 2 ) → A

User Mike McAllister
by
5.0k points
2 votes

Answer:

B.) (0,1)

Hope this helps : )

User Enzo Tran
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.